Exercise - 01 Method of Differentiation: Check Your Grasp

Download as pdf or txt
Download as pdf or txt
You are on page 1of 7

METHOD OF DIFFERENTIATION

EXERCISE - 01 CHECK YOUR GRASP




 m

m n

n  

 ( m n )( n  ) ( n  )( m ) ( m )( m n ) 
 2  m 2  m 2  n 2  n 2  2 
 
= 2ƒ(x)g(x) – 2g(x)ƒ (x) = 0
(m  n )( n   )(   m ) 
5. x  
= x  ƒ 2(x) + g2(x) = constant
d ƒ 2(5) + g2(5) = 4 + 4 = 8
= x0 = 1  (1) = 0
dx
 ƒ 2(10) + g 2(10) = 8
2 2
1  y / x  23. ƒ(x) = xn
7. cos–1  = loga
 1  y 2 / x 2   ƒ '(x) = nxn-1, ƒ "(x) = n(n–1)xn–2
 y  y  log a ..............................................
 2tan–1   = log a    tan–1   = ƒ ""....... n times(x) = n!
x x 2
y  log a  ƒ '(1) ƒ "(1) ƒ ""........n times (1)
Now ƒ(1) –  – ........
 = tan 
x 2  1! 2! n!
Now differentiating both sides, we get n n(n  1) n!
= 1 –  – ........... = (1 – 1)n = 0
dy 1! 2! n!
x y dy y
dx = 0   1 ƒ '(x) 1 g '(x)
2
dx x 
x ƒ(x)  g(x) 2 ƒ(x) 2 g(x)
8. ƒ(x) = (x – 1)100. (x – 2)2.99. (x – 3)3.98.....(x–100)100.1 28. lim = lim
x 4
x 2 x 4 1
Take log & than differentiate we get 2 x
ƒ '(x) 1.100 2.99 3.98 100.1
Now    +.... 9 6
ƒ(x) x 1 x  2 x  3 x  100 
= 2 2 =
ƒ '(101) 3 2
= 1 + 2 + 3 ..... + 100 = 5050 1
ƒ(101) 2
ƒ(101) 1 29. y = e–x & y = e–xsinx
 
ƒ '(101) 5050
y' = –e –x ...(i) & y' = –e–x(sinx – cosx) ...(ii)
x x(b  y) equating (i) & (ii)
10. y= y=
x ab  ay  x
a e –x(1 – sinx + cosx) = 0
by
e–x  0  1 – sinx + cosx = 0
 aby + ay2 + xy = xb + xy
x x x
dy dy dy b  2cos2 = 2sin cos
 ab + 2ay = b  = 2 2 2
dx dx dx ab  2ay
13. 2 2 2 2
x (1 + y) = y (1 + x)  x – y + xy(x – y) = 0 x  sin x  cos x   0 
 2cos   x= ,
 (x – y) (x + y + xy) = 0 2  2 2  2
Now x  y [does not satisfy the given equation] slope can be e  / 2 & –e –
x
 x + y + xy = 0  y = 33. f–1(x) = g(x)  x = f(g(x))
1x
Differentiating both sides,
dy (1  x)  x 1
  2
 1
dx (1  x) (1  x) 2 1 = f'(g(x)) g'(x)  g'(x) =
18. g(x) = ƒ –1(x)  ƒog(x) = x f '(g(x))

1 No w f'(x) = 2x + 3
 ƒ '(g(x))g'(x) = 1  g'(x) =
ƒ '(g(x)) 1 1
So g'(x) =  g'(1) =
1 1 1a 2
2g(x)  3 2(g(1))  3
 g'(2) =   10
ƒ '(g(2)) ƒ '(a) a gof(x) = x  g'(f(x)) f'(x) = 1
22. ƒ '(x) = g(x) and g'(x) = –ƒ(x) f(x) = 1 at x = 1 & f'(1) = 5
d g'(1)f'(1) = 1  g'(1) = 1/5
No w [ƒ 2(x) + g2(x)] = 2ƒ(x) ƒ '(x) + 2g(x) g'(x)
dx
EXERCISE - 02 BRAIN TEASERS
dy dy  1 1  1 1
2. y2 = p(x)    2y = p'(x)  
dx dx  y  x y  x  = yx yx
d2 y  dy 
2

 2y 2 + 2   = p"(x) dy yx  yx


dx  dx  
2
dx yx  yx
d2 y  p '(x) 
 2y 2 + 2  = p"(x)
dx  2y  x y  y2  x2 2x
=  = 2
d2 y y  y2  x2 x c
3
 4y + (p'(x)) 2 = 2y 2p"(x)
dx 2 (By rationalizing Nr. or Dr.)
2
d y 14.  = xlim xm (n x)n
 4y3 = 2p(x)p"(x) – (p'(x))2 0 
dx 2
( nx) n    
d  3 d2 y  = lim as x  0   
 2 y x 0 (1 / x) m   
dx  dx 2  

1 n( nx) n 1 1 / x
= [2p'(x)p"(x)+2p(x)p'"(x) – 2p'(x)p"(x)]   lim (applying L'Hopital's rule)
2 x 0 mx  m 1
d  3 d2 y 
 2 y = p(x)p'"(x) n( nx) n 1
dx  dx 2   lim m
dy 1
x 0 m 1 / x 
3. 
dx dx Again differentiating (n – 1) times
dy
n!
d  dy  d  1  d  1  dy   lim
  x 0  1 
  
dx  dx  dx  dx dy  dy  dx dy  dx
  ( 1) n m n  m 
x 
1 d 2 x dy  = 0
= – 2
. .
 dx dy  dy 2 dx x
log sin
dy d2 y 15. lim log cos x . 2
x 0
Now put the value of & in x log sin x
dx dx 2 log cos
2
d2 y dy x
2 + y = 0 log sin
dx dx log cos x 2
2 = lim lim
x × x 0 log sin x
d2 x  dx  x 0
log cos
On solving we get 2 – y = 0
dy  dy  2
x
11. yx  yx = c cot 2
tan x
= lim
x 0
× lim
x 0
2 = lim tan x  4
1  dy  1  dy  x cot x x 0 x
  1 +   1 = 0 tan tan 2
  2 2
2 y  x dx 2 yx dx

EXERCISE - 03 MISCELLANEOUS TYPE QUESTIONS


True and False : 1 log (log x)
1
u(x) (B) f(x) = log x 2 log(x ) = log x(log x)=
2 2 log x
1. =7 u(x) = 7v(x)
v(x)
 1 1 log(log(x)) 
pq log x. . 
u '(x)  
= 7 = p & q = 0 so =1 f'(x) = 1  log x x x

v '(x) pq 2 (logx) 2

Match the Column :
1  1  log .(log(x)) 
2. (A) f'(x) = 3x2 + 1   f'(x2 + 1) = 3(x2 + 1)2 +1 = e
  f'(e ) = 0
2  x(log x) 2
f'(x2 + 1) at x = 0 is 4
  x hence range is (–, 1]
(C) y = ntan   
4 2 g(0)  g(0)
3. g(0) =  2g(0) = kg(0)
  x 2 k
sec    1 1
dy 1  4 2
 =   g(0) = 0 (as k  2)
dx 2   x     cos x
tan    sin   x 
 4 2 2 xh
= sec x g   g x 
 1 
Hence p = 0 g'(x) = lim
h 0
h
(D) f(x) = |x3 – x2 + x – 1| sin x
f(x) = |(x2 + 1) (x – 1)| sin x g(x)  g(h)
 g(x)
= (x2 + 1) (x – 1) sin x when x  1 = lim
h 0
1
2
= –(x + 1) (x – 1) sinx when x < 1 h
Now 28f(f()) = 0
g  h   g 0 
 At x = 0 = lim
h 0
= g'(0) = 
h
f'(x) = –[2x(x–1) sinx + (x2 + 1)
sin x + (x2 + 1) (x – 1) cos x] g(x) = x + c
4f'(0) = 4
 g(x) = x [g(0) = 0]
Assertion and Reason :
No w x2 + x + 1 = x  x2 + (1 – ) x + 1 = 0
1. Hint : Statement I : f(x) is constant function
For concident pt. D = 0
Statement II : It is true (1 – )2 – 4 = 0
Comprehension # 1 :   = 3, –1
f(x + y) – f(x) = f(y) – 1 + 2xy
Comprehension # 3 :
 f(0 + 0) – f(0) = f(0) – 1 + 2(0) (0)  f(0) = 1
and f'(0) = 1 (given) f(  a  h)  f( a)
1. LHD = hlim
0 
h
f(x  h)  f(x)  f(h)  1 2xh 
Also f'(x)= lim = lim  h   f(a  h)  f(a) f(a  h)  f(a)
h 0 h h  0 h  = hlim = hlim
0  0 
h h
f(h)  f(0)
= lim + 2x = f'(0) + 2x f '(a)  f '(a  h) f '(a)  f '(h  a)
h 0 h 2. RHD = hlim0 
=
h h
f'(x) = 1 + 2x
Since derivative of even function is odd & vice versa.
Integrate it
f(  x)  f(  x  h) f(  x  h)  f(  x)
f(x) = x2 + x + c 3. lim = lim
h 0 h h  0 h
f(x) = x2 + x + 1 [f(0) = 1  c = 1]
= f'(– x) ... (i)
1. n(x + x + 1)  Domain R
2

f(x)  f(x  h)
2. y = log3/4(x2 + x + 1) and lim = – f'(x) ... (ii)
h 0 h
3 from (i) and (ii) f'(x) is odd function and hence f(x) is
Now x2 + x + 1  even function.
4

EXERCISE - 04 [A] CONCEPTUAL SUBJECTIVE EXERCISE


5. ƒ1(x) = e ƒ 0 ( x ) = ex = fn(x) . f(n–2)x..............f1(x)
2
ƒ2(x) = e ƒ1 ( x ) = e e
x
x 1
6. y =  x x 2  1 + n x  x 2  1
ex
2 2
ƒ3(x) = e e
e......( n 1 ) times ( x )
2y = x2 + x x 2  1  n  x  x 2  1  .....(i)
ee
similarly fn(x) = e
2x
1
d d 2x 2 2 x2  1
No w  fn (x)  = e fn 1 ( x ) . dx (e fn 1 ( x ) ) 2y' = 2x + x 2  1 + 
dx 2 x 12
x  x2  1
On differentiating it completely we get
x2 1
2y' = 2x + 
d x 1 +
2
2
x 1 2
x 1
 fn (x)  = e fn 1 ( x ) .e f( n 2 ) ( x ) .e f( n 3 ) ( x ) .......e f0 ( x )
dx
= 2x + x2  1 + x2  1 dx
14. = sec tan + sin = tan x2  4
d
y' =  x  x  1 
2

dy
Put the value of x + x 2  1 in (i) = nsecn–1 . sec . tan + ncosn–1 (–sin)
d
2y = xy' + n y'
 y 
= n tan [secn + cosn] = ntan y2  4
sin 1  
 x 2  y2 
11. x2  y2 = e 2
2  y  4
2
 dy 
    n  2
1  y  dx x  4
 n (x2 + y2) = sin–1  x2  y2 
2  
(a  b cos x)x  c sin x
17. lim 1
 2 2 y(2x  2yy ') 
x 0 x5
 x  y y '  Now using L’ hospital rule
1  2x  2yy ' 1  2 x2  y2 
 
2  x2  y2  y2  2
x y 2

1  bx sin x  (a  b cos x)  c cos x
x  y2
2 lim
x 0 5x4
For limit to exist a + b – c = 0 ........(i)
x2  y2  (x 2  y 2 )y ' y(x  yy ') 
 x + yy' =   b(sin x  x cos x)  b sin x  c sin x
x  x2  y2  Again lim
x 0 20 x 3
 x + yy' = xy' – y
b(cos x  cos x  x sin x)  b cos x  c cos x
= lim
Again on differentiation we get x 0 60 x 2

2(x 2  y 2 )  3b  c  cos x  xb sin x


y" = = lim
(x  y) 3 x 0 60x 2
12. f(x) = x2 – 4x – 3 & f(x) = 9 For limit to exist –3b + c = 0 ...........(ii)
For x = 6, – 2
xb sin x
 x = 6 (x > 2)  l im 1
x 0 60x 2
Now y = f(x)  f–1(y) = x
 g(y) = x  b = 60, c = 180, a = 120

dx 1 1 log| tan 2x|  sec 2 2x tan x 


g'(y) =   21. l im = l im 2  . = 1

dy 2x  4 8 x  0 log| tan x| x 0  sec 2 x tan 2x 

EXERCISE - 04 [B] BRAIN STORMING SUBJECTIVE EXERCISE


1 dx 1 d2 y d  dy  dx
1. x=   2 =  sin x  .
z dz z dz 2
dx dx dz
dy dy dz dy
Now  . = ( z 2 ) d2 y  d2 y dy 
dx dz dx dz   sin x 2  cos x  sin x ........(i)
dz 2  dx dx 
d dy ' dz dy d 2 z
(y ')  .  .
dx dz dx dz dx 2 d2 y 2 d2 y dy
2
 sin x 2
+ sinx cosx
dz dx dx
d2 y 3 dy
2
4d y
 2z . + z
dx 2 dz dz 2 d2 y d2 y dy
cosec 2 x =  cot x
d2 f dy d2 y dz 2 dx 2 dx
 2
= 2z3 + z4 2 Now put value from given equation
dx dz dz
 x d2 y
3. z = n  tan  cosec2x + 4ycosec 2x = 0
2 dz 2
dz 1 dy dy dx dy d2 y
 Now = . = sin x  4y  0
dx sin x dz dx dz dx dz 2
4. f(2x) = f '(x)f "(x) 7. ƒ(x) = c(x – )2

Let the degree of ‘f’ be n. A (x) B(x) C(x)


Comparing highest power on both sides F(x) = A (  ) B(  ) C (  )
A '(  ) B '(  ) C '(  )
n = n – 1 + n – 2 n = 3
Now F() = 0  (x – ) is root of F(x).
Let f(x) = a0x3 + a1x2 + a2x + a3
f(2x) = f'(x)f''(x) A '(x) B '(x) C '(x)
F'(x) = A (  ) B(  ) C(  )
 (8a 0x3 + 4a 1x 2 + 2a 2x + a 3)
A '(  ) B '(  ) C '(  )
= (3a 0x 2 + 2a 1x + a 2)(6a 0x + 2a 1)
Now F'() = 0 x –  is a factor of F '(x). So (x – )
Comparing coefficient of x 3 must be repeated at least two times in F(x).
 F(x) is divisible by f(x).
4
8a0 = 18a02  a0 =
9 1 2 e 2 x  1  2x
11. ƒ(x) =  2x = lim
Rest all are zero x e 1 x 0 x(e 2 x  1)

4 3 2e 2 x  2
 f(x) = x = lim (by L–hopital rule)
9 x 0 e2 x  1  x(2e 2 x )

X sX tX 4e 2 x
= lim  1  ƒ(0) = 1
5. X1 sX 1  s1 X t1 X  tX 1
x 0 2e 2 x  2e 2 x  4e 2 x .x

X2 sX 2  2s1 X 1  Xs 2 tX 2  2X 1 t1  Xt 2 1 2
 2h 1
ƒ '(0+) = lim 0  h e 1
C 2  C 2  sC 1 , C 3  C 3 – tC 1  h 0 h

e 2 h  1  2h  h(e 2 h  1)
X 0 0 = lim
h 0 h 2 (e 2 h  1)
= X1 Xs1 Xt1
X2 Xs 2  2s1 X 1 Xt 2  2t1 X 1 4h 2
1  2h  ......  1  2h  h(e 2 h  1)
= lim 2!
Xs1 Xt1 h 0 h 2 (e 2 h  1)
= X
Xs 2  2s1 X 1 Xt 2  2t 1 X 1 8h 3 (2h)2 8h 3
(2h 2   ....)  h(2h   ...) 1
= lim 3! 2! 3! = –
s1 t1 h 0 2h  2 3
= X2 h 2 (2h   ....)
Xs 2  2s1 X 1 Xt 2  2t 1 X 1 2!
(R2  R2 – 2 X1R1) 1
Similarly ƒ '(0–) =  .
3
s1 t1 s1 t1
= X2 = X3
Xs 2 Xt 2 s2 t2
EXERCISE - 05 [A] JEE-[MAIN] : PREVIOUS YEAR QUESTIONS

log x y  ......  dy
3. y = log y x y = 8. x = ey e x > 0 = ?
log y dx
y × logy = logx  dy 
x = e y+x 1 = e y+x  1  
dy 1 dy 1  dx 
logy + y × × = 1 dy 1x dy
dx y dx x = 1 + =
x dx x dx
dy 1 dy 1
(logy + 1) =  10.  x x 2  2 cot y x x  1  0
dx x dx x(1  log y )
at x  1,
4. x = 3cos – 2cos3   y = 3sin – 2sin3 2 cot y  4 cot 2 y  4 
xx  1  cot y  cosec y
dx 2 
= –3sin + 6cos 2 × sin  
= cot y  cosec y
d  y  2
dy x x = cot y + cosec y
= 3cos – 6sin2 cos diff. w.r. to x
d
dy
dy 3 cos   6 sin 2  cos  xx (1 + logx) = [–cosec 2y – cosec y cot y]
= dx
dx 3 sin   6 cos 2  sin 
dy
cos   2 sin 2  cos  1 = – cosec y [cosec y + cot y]
= 2
= cot dx
 sin   2 cos  sin 
dy
6. f(x) = x n = –1
dx
f '(1) f "(1) f "'(1) (–1) x f n (1) 11. g(x) = [f(2f(x) + 2)] 2
f(1) – + – ....
1! 2! 3! n! g'(x) = 2f (2f(x) + 2) f ' (2f(x) + 2) 2f '(x)
put n = 1
Put x = 0
f '(1)
f(x) = x for series f(1) – = 0 g'(0) = 2f(2f(0) + 2) f '(2f(0) + 2) 2f '(0)
1
f(1) = 1 put n = 2 = 2f(2(–1) + 2) f '(2(–1) + 2) 2f '(0)
f(x) = x 2
f'(x) = 2x f"(x) = 2 = 2f(0) f '(0) 2f '(0)
f(1) = 1 = 4(–1) (1) (1) = –4
f '(1) f "(1) 2 1 1
so series = f(1) – + = 1 – 2 + = 0 d   dy   d   dy   dx
1! 2! 2 12.        .
Put x = 3 f(x) = x 3 dy   dx   dy   dx   dy
   
2
f'(x) = 3x f"(x) = 6x 3
2
f(1) = 1 f"'(x) = 6  dy  d 2 x dx  d 2 y   dy 
   . 2 .   2  
f '(1) f" (1) f "'(1)  dx  dx
series f(1) – + –  dx  dx dy   
1! 2! 3!
6 6 13. y = sec(tan –1 x) = 1  x 2
= 1 – 3 + – = 0
2 6
7. f(x) is a polynomial function dy x dy 1
  
f(x) = ax 2 + bx + c f(1) = f(–1) dx 1  x2 dx x 1 2
a + b + c = a – b + c b = 0
a c
a, b, c in A.P. b = a  –c
2
f(x) = ax 2 + bx + c f' (x) = 2ax + b
2
f' (a) = 2a + b f'(c) = 2ac + b
f'(b) = 2ab + b then f'(a), f'(b), f'(c)
f'(b) = 0 f'(a) = 2a 2 f'(c) = –2a 2
so that f '(a), f '(b), f '(c) are in A.P.
EXERCISE - 05 [B] JEE-[ADVANCED] : PREVIOUS YEAR QUESTIONS

2. (b) Let P(x) = ax2 + bx + c


(b) L im
 g(x ) cos x  g(0) 
P(0) = 0  c = 0
x 0 sin x
g '(x) cos x  g(x) sin x
P(1) = 1  a + b = 1 = L im 0
x 0 cos x
 P(x) = (1 – a)x2 + ax Now f(x) = g(x) sin x
P'(x) = 2 (1 – a)x + a > 0 f'(x) = g'(x) sinx + g(x) cosx
 f'(0) = 0
put x = 0, a > 0
f''(x) = g''(x) sinx + g'(x) cosx – g(x) sinx
x = 1, a < 2 + g'(x) cosx
2
S = {(1 – a) x + ax ; 0 < a < 2}. f''(0) = 0 
Given limit = f''(0) & also f'(0) = g(0)
5. (a) g(x + 1) = log(f(x + 1)) = log x + log f(x) So S(I) & S(II) both are correct but S(II) is
 g(x + 1) = log x + g(x) not correct explaination of S(I)
 g(x + 1) – g(x) = log x 6. f(x) = x3 + ex/2, g(x) = f–1 (x)
 g'(f(x)).f'(x) = 1
1
 g'(x + 1) – g'(x) = Put f(x) =1  x3 + ex/2 =1
x  x =0
1 1
 g"(x + 1) – g"(x) = – 2  g' (1).f'(0) = 1, f'(x) = 3x2 + ex/2.
x 2
 g'(1) =2
 1  1
 g"  1   – g"   = – 4  sin  
 2   2 7. Let ƒ( )  sin  where   tan 1  
 cos 2  
 1  1 4
 g"  2   – g"  1   = –
 2 2 9
...................................................
sin 
 tan  
1 1 –4 cos 2 
 
g"  N   – g"  N –  =
 2 2 (2N  1)2 sin      
By adding  sin    tan       ,  
cos    4 4 
 1  1
Hence g"  N   – g"    ƒ( )  tan 
 2  2
d(ƒ( ))
 1 1   1
= – 4  1   ......  2 d(tan )
 9 (2N  1) 

You might also like